The Macroeconomic Uncertainty Premium in the Corporate Bond Market. (6th August 2021) - Bali, Turan G.; Subrahmanyam, Avanidhar; Wen, Quan
Abstract: We examine the role of macroeconomic uncertainty in the cross section of corporate bonds and find a significant uncertainty premium for both investment-grade (IG) (0.40% per month) and non-investment-grade (NIG) (0.81% per month) bonds. The economic-uncertainty premium declines as we progressively remove downgraded bonds, indicating that the premium represents an increase in required returns for bonds with higher credit and macroeconomic risk. The economic-uncertainty premia vary across equities and bonds in a manner consistent with the heterogeneous risk-aversion levels of dominant players in equities (retail investors) versus bonds (institutional investors).